2014
DOI: 10.1093/eurpub/cku078
|View full text |Cite
|
Sign up to set email alerts
|

Multiple risk behaviour in adolescence and socio-economic status: findings from a UK birth cohort

Abstract: Background. Patterns of risk behaviour during teenage years may vary by socio-economic status (SES). We aimed to examine possible associations between individual and multiple risk behaviours and three measures of SES in mid-adolescence. Methods. The sample (n = 6406) comprised participants from the Avon Longitudinal Study of Parents and Children, a UK birth cohort. Thirteen risk behaviours spanning sexual health, substance use, self-harm, vehicle-related injury, criminality and physical inactivity were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 23 publications
2
87
3
2
Order By: Relevance
“…We also conducted subgroup analyses to investigate whether results differed when education was measured using paternal, maternal, or parental education; no important differences were found. In England, Kipping et al [28] investigated associations between SES, measured by social class, maternal education, and family income. They found that, after mutual adjustment for other SES variables, family income and maternal education were both inversely associated with TV viewing time [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also conducted subgroup analyses to investigate whether results differed when education was measured using paternal, maternal, or parental education; no important differences were found. In England, Kipping et al [28] investigated associations between SES, measured by social class, maternal education, and family income. They found that, after mutual adjustment for other SES variables, family income and maternal education were both inversely associated with TV viewing time [28].…”
Section: Discussionmentioning
confidence: 99%
“…In England, Kipping et al [28] investigated associations between SES, measured by social class, maternal education, and family income. They found that, after mutual adjustment for other SES variables, family income and maternal education were both inversely associated with TV viewing time [28]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the existing studies also yielded controversial results (Adhikari & Summerill, 2000;Alonso et al, 2004;Grinshpoon, Marom, Weizman, & Ponizovsky, 2007;Kipping, Smith, Heron, Hickman, & Campbell, 2015;Legleye, Beck, Khlat, Peretti-Watel, & Chau, 2012;Sandwijk, Cohen, & Langemeijer, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The inverse relationship between risk behaviour and socioeconomic status (SES) has been widely reported [810]. In response, strategies to improve health behaviour of young people have often targeted low SES groups.…”
Section: Introductionmentioning
confidence: 99%